WORDWALL WEBSITE MEDIA: ENHANCING STUDENTS' ENGLISH VOCABULARY MASTERY AND BOOSTING STUDENTS’ MOTIVATION TO LEARN ENGLISH - Hakim, Nisa Halisa; Herusatoto, Hesthi; Setiarini, Sri Endah (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2023)
This descriptive quantitative research investigated the use of Wordwall website media to assist students to learn English vocabulary and to stimulate students’ motivation to learn. Grade 8 Junior Hight School students of Taman Dewasa Cangkringan in Yogyakarta who felt uninterested in learning English and found learning vocabulary difficult were the subjects of this research. Data were collected through observations, treatments, a pre-test, a post-test, questionnaires, and interviews. It was found out that the majority of the students achieved better scores in the post-test​​. Wordwall website media could help students acquire vocabulary and raise students’ enthusiasm to learn English. The media was stimulating and engaging and it facilitated students in the learning process.